(untitled) (Pedagogy of Higher and Secondary Education, 2022)
Compex support of pupis of different age groups provides the mechanism successful psychological adaptation of children to requirements and conditions of the school environment. Support is considered as system of professional work of the director of studies, the psychologist, the teacher, the sociologist, the doctor, directed on creation of socaly-psychological conditions for successfal training and psychologcal development of the chid in system of school interaction.